Medicaid Reimbursement for Common Spine Procedures: Are Compensation Rates Consistent?. Issue 22 (15th November 2019) - Casper, David S.; Schroeder, Gregory D.; McKenzie, James; Zmistowski, Benjamin; Vatson, Jayanth; Mangan, John; Stull, Justin; Kurd, Mark; Rihn, Jeffrey A.; Anderson, D. Greg; Kaye, David I.; Radcliff, Kris; et al.
Abstract : Study Design: Health Services Research. Objective: The purpose of this study is to determine the variability of Medicaid (MCD) reimbursement for patients who require spine procedures, and to assess how this compares to regional Medicare (MCR) reimbursement as a marker of access to spine surgery. Summary of Background Data: The current health care environment includes two major forms of government reimbursement: MCD and MCR, which are regulated and funded by the state and federal government, respectively. Methods: MCD reimbursement rates from each state were obtained for eight spine procedures, utilizing online web searches: anterior cervical decompression and fusion, posterior cervical decompression and fusion, posterior lumbar decompression, single-level posterior lumbar fusion, posterior fusion for deformity (less than six levels; six to 12 levels; 13+ levels), and lumbar microdiscectomy. Discrepancy in reimbursement for these procedures on a state-to-state basis, as well as overall differences in MCD versus MCR reimbursement, was determined. Procedures were examined to identify whether certain surgical interventions have greater discrepancy in reimbursement. Results: The average MCD reimbursement was 78.4% of that for MCR. However, there was significant variation between states (38.8%–140% of MCR for the combined eight procedures). On average, New York, New Jersey, Florida, and Rhode Island provided MCD reimbursements <50% of MCR reimbursements in the region. In total, 20 and 42 states provided <75% and 100% of MCR reimbursements, respectively. Based upon relative reimbursement, MCD appears to value microdiscectomy (84.1% of MCR; P  = 0.10) over other elective spine procedures. Microdiscectomy also had the most interstate variation in MCD reimbursement: 39.0% to 207.0% of MCR. Conclusion: Large disparities were found between MCR and MCD when comparing identical procedures. Further research is necessary to fully understand the effect of these significant differences. However, it is likely that these discrepancies lead to suboptimal access to necessary spine care. Level of Evidence: 4 Abstract : Large disparities exist between Medicare and Medicaid reimbursement, when comparing identical procedures. Additionally, there is a large variability in reimbursement for spine procedures from one state to another. It is likely that these discrepancies lead to suboptimal access to necessary spine care.